circNrxn2 Promoted WAT Browning via Sponging miR-103 to Relieve Its Inhibition of FGF10 in HFD Mice - Tiantian Zhang; Zhenzhen Zhang; Tianyu Xia; Chenlong Liu; Chao Sun (Elsevier, 2019)
The accumulation of excess white adipose tissue (WAT) has harmful consequences on metabolic health. WAT browning confers beneficial effects on adiposity, insulin resistance, and hyperlipidemia. In this study, it was found out that circNrxn2 sponged miR-103 and enhanced FGF10 levels in HFD mice WAT. We discovered that circNrxn2 promoted WAT browning and mitochondria functions. Furthermore, circNrxn2 also increased M2 macrophage polarization in HFD mouse adipose tissue, and the PPARγ signaling pathway participated in these biological processes. Moreover, eliminating adipose tissue macrophages (ATMs) by clodronate-crippled circNrxn2 promoted WAT browning, and the simulation co-culture of macrophages and adipocytes results suggested that circNrxn2 promoted WAT browning through increasing M2 macrophage polarization. Our finding revealed that circNrxn2 acted as an endogenous miR-103 sponge, blocked miR-103 effects, and relieved its inhibition of FGF10 expression to promote WAT browning through increasing M2 macrophage polarization. This study provides a good therapeutic strategy for treating obesity and improving obesity-related metabolic disorders. Keywords: circNrxn2, miR-103, FGF10, adipose tissue macrophages, white adipose tissue browning